Primary Isolated Lymphoma of the Fourth Ventricle in an Immunocompetent Patient - Rakan Bokhari; Ahmad Ghanem; Mahmoud Alahwal; Saleh Baeesa (Case Reports in Oncological Medicine)
Primary central nervous lymphoma (PCNSL) is a rare variant of extranodal non-Hodgkin's lymphoma with a especially poor prognosis. The diagnosis is usually encountered in immunodeficient patients but is also encountered, albeit uncommonly, in the immunocompetent. We present a 50-year-old male who developed signs and symptoms of increased intracranial pressure. Imaging revealed the presence of a fourth ventricle mass with obstructive hydrocephalus. First, the patient underwent emergency endoscopic third ventriculostomy followed, few days later, by complete tumor resection via a posterior fossa craniotomy. Postoperative histopathology revealed the lesion to be a PCNSL. He received adjuvant chemotherapy and radiation and remained with no recurrence on regular imaging studies for 18-month followup. We report herein the fourth case of isolated PCNSL lesion to the fourth ventricle in the literature and provide the rationale for our belief that craniotomy and tumor resection, if feasible, should be the initial line of management in similar cases to relieve hydrocephalus and achieve the diagnosis.